Functional chronic venous disease: A systematic review. (October 2017) - Serra, Raffaele; Andreucci, Michele; De Caridi, Giovanni; Massara, Mafalda; Mastroroberto, Pasquale; de Franciscis, Stefano
Objectives: Functional chronic venous disease is an underestimated syndrome quite present in the general population. It affects up to 20% of the general population and is based on the presence of venous symptoms without instrumental evidence of anatomic and morphologic damage. The aim of this review article is to provide the reader with the most updated information on this phenomenon. Methods: Medline and Scopus databases were searched without time limit using the key-word: 'Functional chronic venous disease of legs', C0s patients. We decided to include all the studies conducted about functional chronic venous disease. Randomised trials, cohort studies and reviews were contemplated in order to give a breadth of clinical data. Only publications in English were considered. We excluded all the studies with insufficient statistical analysis, possible biases and contradictions, not clear end-points, inconsistent or arbitrary conclusions. Results: Of the 326 records found, after removal of 68 duplicates, 143 matched our inclusion criteria. After reading the full-text articles, 133 manuscripts were excluded. Ten full text articles were assessed for eligibility and four studies were excluded because of the following reasons: (a) no specific or important content and (b) insufficient data; the final set included six articles. Conclusions: Functional chronic venous disease is a complex syndrome and further evidences are needed in order to assess the pathophysiology, the morbidity and the correct treatment of this venous dysfunction.